A randomized, double-blind, placebo-controlled, dose-escalation study of the safety and efficacy of INCB039110, an oral janus kinase 1 inhibitor, in patients with stable, chronic plaque psoriasis. (3rd July 2016) - Bissonnette, Robert; Luchi, Monica; Fidelus-Gort, Rosanne; Jackson, Shawnta; Zhang, Haifeng; Flores, Robert; Newton, Robert; Scherle, Peggy; Yeleswaram, Swamy; Chen, Xuejun; Menter, Alan
Abstract: Background : Chronic plaque psoriasis is partially mediated by elevation of proinflammatory cytokines, including several within the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway. Objective: To evaluate the safety and efficacy of the oral selective JAK1 inhibitor INCB039110 in stable, chronic plaque psoriasis. Methods : This was a phase 2, randomized, double-blind, placebo-controlled, dose-escalation study of INCB039110 (100 mg once daily, 200 mg once daily, 200 mg twice daily and 600 mg once daily) for 28 days. The primary endpoint was mean percent change from baseline in the static Physician Global Assessment (sPGA) at day 28. The protocol was institutional review board approved. Results : Of 50 patients, 48 completed the study. At day 28, mean percent reduction from baseline in sPGA was 22.2% for INCB039110 100 mg once daily ( p = 0.270 vs. placebo), 29.4% for 200 mg once daily ( p = 0.118), 35.2% for 200 mg twice daily ( p = 0.053), 42.4% for 600 mg once daily ( p = 0.003) and 12.5% for placebo. Across groups, 11.1% to 45.5% achieved an sPGA score of 1 versus 0% for placebo. INCB039110 was generally well tolerated; the most common treatment-emergent adverse event was nasopharyngitis (18.4%). Conclusion : INCB039110 produced significant improvements in sPGA, demonstrating proof of concept in chronic plaque psoriasis.